2020
DOI: 10.1210/clinem/dgaa127
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Maternal Normal Range HbA1c Values and Adverse Birth Outcomes

Abstract: Context Higher blood glucose level during gestational periods has been consistently associated with increased risk of adverse birth outcomes. Evidence regarding the association between higher glycated hemoglobin A1c (HbA1c) within the normal range and adverse birth outcomes is limited. Objective We aimed to examine the association between HbA1c within the normal range and the risk of adverse birth outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Therefore, we still need to develop a recommended pregnancy weight gain value for Chinese women. Other studies have confirmed that, in addition to FPG, increased postprandial blood glucose and glycosylated hemoglobin are significantly associated with macrosomia in pregnant women with GDM [ 27 – 29 ]. Maternal hyperglycemia may cause morphological changes in the placentas of pregnant women.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we still need to develop a recommended pregnancy weight gain value for Chinese women. Other studies have confirmed that, in addition to FPG, increased postprandial blood glucose and glycosylated hemoglobin are significantly associated with macrosomia in pregnant women with GDM [ 27 – 29 ]. Maternal hyperglycemia may cause morphological changes in the placentas of pregnant women.…”
Section: Discussionmentioning
confidence: 95%
“…The opinion that HbA1c might be slightly lower in normal pregnancies than in normal nonpregnant women has been raised previously [ 11 ]. However, whether the pregnancy is related to HbA1c levels in nondiabetic women remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have varied widely in the selection of variables for adjustment. 7 , 17 Given this uncertainty, we explored univariate and multivariate associations between HbA1c and a number of possible confounders, chosen for their plausible association with HbA1c and their known association with pregnancy outcomes. We saw few associations in our data; just three factors met criteria for confounding: maternal age, BMI and sustained smoking at time of recruitment ( Supplementary Table S1 and Supplementary Figure S1 , available as Supplementary data at IJE online).…”
Section: Methodsmentioning
confidence: 99%
“…Until very recently, there has been little epidemiological research to explore this possibility. 2 , 17 Only a handful of epidemiological studies have studied HbA1c in pregnancy in women without diabetes. 7 , 16–21 …”
Section: Introductionmentioning
confidence: 99%